COMPARATIVE ANALYSIS OF ANALGESIC ONSET AND DURATION: BUPIVACAINE WITH FENTANYL VS. BUPIVACAINE WITH MEPERIDINE IN SPINAL ANESTHESIA FOR CESAREAN SECTION - Napitupulu, Olivia Des Vinca Albahana; Arifin, Hasanul; Nasution, Sani P (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
This study aimed to compare the onset and duration of analgesia in spinal anesthesia for cesarean section using hyperbaric bupivacaine combined with fentanyl or with meperidine. A double-blind randomized controlled trial was conducted involving sixty patients undergoing either elective or emergency cesarean section at Jejaring Hospital and H. Adam Malik General Hospital Medan. Patients were randomly assigned to receive hyperbaric bupivacaine with fentanyl or hyperbaric bupivacaine with meperidine, and the data were analyzed using appropriate statistical methods to examine differences between the groups. The findings revealed that the combination of bupivacaine with fentanyl produced a faster onset of analgesia compared to bupivacaine with meperidine, whereas the combination with meperidine provided a longer duration of analgesia. Both combinations were effective in achieving intraoperative and postoperative pain control, each offering distinct advantages. The study concludes that the choice of spinal anesthesia combination can be tailored to the clinical needs of patients, with fentanyl being preferable for rapid onset and meperidine offering prolonged analgesia.